How to hug a porcupine : negotiating the prickly points of the tween years - Ross, Julie A., 1959- (McGraw-Hill, 2008)
Yesterday, your child was a sweet eight-year-old. Today, a moody, disrespectful twelve-year-old. What happened ? And more important, how do you handle it ? How you respond to these whirlwind changes will not only affect your child's behavior now but will determine how he or she turns out later. Julie. A. ross, Executive Director of Parenting Horizons, shows you exactly what's going on with your child and provides all the tools you need to correctly handle even the prickliest tween porcupine.